Developing Writing Module for the Fourth-Semester Learners of English Department at State Islamic Institute of Palopo - Andi Tenrisanna Syam (State Islamic University Sultan Aji Muhammad Idris Samarinda, 2020)
This research aimed to develop an appropriate module based on the writing needs of the learners. The author took the fourth-semester learners of the English Department at the State Islamic Institute of Palopo in the academic year 2018/2019. The author involved 40 learners as her participants. The method of the research was Research and Development. The author used the ADDIE model. The ADDIE model consisted of five stages, namely analysis, design, develop, implementation and evaluation. The instruments of the research were questionnaires and documents. The data were analyzed quantitatively qualitatively. The results of the content, the design, and the media experts validation showed that the module got good and very good category. The writing I module quality based on the learners’ response in the field try-out showed that 75% of learners very agree and 25% of learners agree with the materials presented in the module. The result of this research hopefully gives a contribution to some parties, especially to the writing I lecturers and to the other researchers.